Modification of the Polaron sputter-coater unit for glow-discharge activation of carbon support films - Benada, O; Pokorný, V (Journal of electron microscopy technique, 1990)
We describe a modification of the Polaron sputter-coater unit series 11 HD enabling activation of carbon support films for electron microscopy of macromolecules and macromolecular assemblies. The modification is simple and the device can be used in two modes, for sputter-coating of SEM samples and for glow-discharge activation of carbon support films. Examples of protein-free spreading of DNA and negative staining of bacteriophage particles on activated carbon support films are presented.
Keywords: plazmidy; uhlík; Plasmids; DNA, Bacterial; DNA bakterií; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Bacteriophages; Carbon; bakteriofágy